The Effect of Green Accounting and Islamic Corporate Social Responsibility on Sustainability Performance in Manufacturing Companies Listed on the Jakarta Index (2020–2023) - Via yunita; N. Nurlaili; Ersi Sisdianto (Golden Ratio of Auditing Research, 2026)
This study aims to evaluate the extent to which green accounting and Islamic Corporate Social Responsibility (ICSR) impact the achievement of sustainable performance in manufacturing companies listed on the Jakarta Islamic Index from 2020 to 2023. Green accounting is a financial reporting approach that incorporates environmental aspects, aiming to enhance corporate transparency and accountability in environmental preservation. On the other hand, ICSR reflects corporate social responsibility based on Islamic principles, which emphasizes the fulfillment of stakeholder rights and the preservation of ecosystem balance. This study employs multiple regression methods using secondary data obtained from annual reports and sustainability reports, and the results are tested using the EViews 10 tool. The results showed that Green Accounting has a negative impact on sustainability performance, while ICSR has a positive and significant effect. Simultaneously, both variables have a significant effect on the company's sustainability performance. These findings offer valuable insights into the integrative role of environmental reporting and Islamic-based social responsibility in promoting corporate sustainability. This study aims to make theoretical and practical contributions to the development of corporate sustainability strategies grounded in Islamic values in Indonesia.